Upcycling of industrial iron scale waste for reutilization as anode material in lithium ion batteries - Gülcan, Mehmet Feryat; Karahan, Billur Deniz (Elsevier BV, 2022)
Abstract In this work, iron scale is used as the starting raw material to produce anode for lithium ion batteries. In this scope, three different samples are fabricated, then their properties are investigated to evaluate their performances. Firstly, the as received scale is washed with water and milled (Sample 1). Then two different modification methods are applied: physically mixing Sample 1 with carbon (Sample 2) and chemically treating Sample 1 with a polysaccharide contained methanol solution, followed by heat treatment (Sample 3). Galvanostatic tests show that the Sample 2 and Sample 3 exhibit 430 mAh g−1 and 573 mAh g−1, after 200th cycle, respectively. SEM observation reveals that Sample 3 has smaller sized particles with a homogeneous morphology. Raman analysis shows the existence of both graphitized and disordered carbon atoms in Sample 3. The improved performance of Sample 3 is believed to be related to its structural and compositional particularities. The approach presented in this article is expected to set an example for future studies to be carried out within the framework of waste valorisation for energy storage applications.
Keywords: Anode Active Material; Iron Scale; Lithium Ion Battery; Waste Valorisation